Penyusunan Tes Hasil Belajar dan Butir Soal PAI Sekolah Dasar - Nadia Putri Anggreini; Ma'mun Hanif (Murabby: Jurnal Pendidikan Islam, 2024)
This research aims to determine the preparation of learning outcomes tests and the preparation of PAI Class V questions at Salit Kajen Elementary School. This research uses a qualitative descriptive approach, namely research whose results are in the form of interpretation. In this research, observations and interviews were carried out. Thus, at the end of this research it will serve as input for PAI teachers at Salit Kajen State Elementary School and can add insight to readers. Based on the research results, it shows that the preparation of the class V PAI learning outcomes test at Salit Kajen State Elementary School is good because the Salit Kajen State Elementary School PAI teacher uses three test methods, namely oral, written and action. Class V students in PAI lessons are always evaluated with tests. The steps for preparing PAI question items at Salit Kajen State Elementary School are carried out sequentially, starting from determining the test objectives, determining the learning outcomes to be tested, preparing the question items, making a grid, making question items related to the grid, and validating. question items, and assemble the questions into a test set.